Adsorption Characteristics and Pore Structure of Organic-Rich Shale With Different Moisture Contents - Liu, Yan; Cao, Qian; Ye, Xin; Dong, Li (Frontiers in Earth Science, 2022)
A moisture equilibration test has been designed to study the pore structure and adsorption capacity of organic-rich shale with different moisture contents. Five humidity environments were artificially controlled to obtain shale samples with different moisture contents. With the moisture equilibration test and N2 adsorption/desorption, the differences in pore structure of samples with different moisture contents were compared and analysed. The results showed that the diameter of 2–10 nm pores decreased with increasing humidity and that the moisture adsorption characteristics conformed to the GAB adsorption model. It is proposed that when moisture enters a sample, monolayer adsorption will first occur because moisture is preferentially adsorbed on the pore surface with strong hydrophilicity, filling in the relatively small pores. Mesopores and micropores play a major role in water adsorption. With increasing humidity, capillary condensation of moisture gradually occurs in pores. Based on the methane isothermal adsorption test of shale samples with different moisture contents, a quantitative linear relationship between the moisture content and methane adsorption capacity of shale samples has been established. It has been determined that the methane adsorption capacity of shale in underwater conditions is less than that of dry samples, and that the rate of decline in the adsorption capacity of different samples under dry and water balance conditions varies greatly. The distribution characteristics of clay minerals are the main controlling factor of the hydrophilicity of shale, which has a certain guiding significance for further accurate evaluation of shale adsorption gas reserves.